Pengaruh Lingkungan Makro terhadap E-Commerce Buah dan Sayuran di Indonesia - Ayu Kumala Sari; Fadilla Ristya Aminda; Herdiana Anggrasari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Currently, the digitalization of services has erased the boundaries between producers and consumers, one of which is by using e-commerce. This service can help solve farmer and stakeholder problems related to inefficient communication. The focus of this research is to determine the influence of Indonesia's macro environment on the development of fruit and vegetable e-commerce in Indonesia. This research uses a qualitative approach with a literature study method with political, economic, social, technological, ecological, and legal variables to describe the macro environment. The relationship between each macro-environmental factor is studied using PESTEL analysis as a potential opportunity and threat to developing vegetable and fruit e-commerce businesses in Indonesia. The study results show that stable Indonesian politics and rapidly growing digital technology in Indonesia support the development of fruit and vegetable e-commerce. However, from an economic, social, ecological, and legal perspective, it has yet to be able to significantly contribute to developing fruit and vegetable e-commerce in Indonesia. Therefore, it is necessary to integrate fruit and vegetable e-commerce with other goods and services the community needs, such as Grabmart from Grab and Gomart from Gojek.